Modelling Emotional Intelligence Development in Entrepreneurs: Strategic Approach - Fedorova, Yuliia; Pilková, Anna; Mikuš, Juraj; Holienka, Marian; Pidlisna, Juliia (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Emotional intelligence (EI) is a key competency for successful entrepreneurship. Interest in the development of EI in education is growing rapidly and requires strengthening the methodological base. A systematic literature review brought together the latest knowledge in different fields and revealed the opportunity for fundamental development of the EI of entrepreneurs. This study aims to provide a detailed description of the 4-component instrumental model of EI development for entrepreneurs (4EIE Model), based on combining the latest knowledge in psychology and entrepreneurship. The 4EIE Model consists of 4 main components (namely Self-Awareness, Self-Management, Social Awareness and Relationship Management), according to the latest version of D. Goleman's mixed model and supporting the development of 15 important entrepreneurial competencies, according to the EntreComp conceptual model. The 4EIE Model is convenient to use in a university environment.